Kebijakan Pangan dan Gizi Nasional dalam Praktik Pemenuhan Pangan Keluarga di Aceh: Analisis Foucauldian tentang Diskursus Kuasa Tubuh Manusia - Nulwita Maliati; Sumarti, Titik; Agusta, Ivanovich; Tanziha, Ikeu (Sodality: Jurnal Sosiologi Pedesaan, 2022)
This article aims to analyze national policies on food and nutrition in the family food fulfillment practices in Aceh. Various programs to address food and nutrition problems have been made but nutrition problems have not been successfully resolved. The results of the 2018 Basic Health Research (Riset Kesehatan Dasar, Riskesdas) showed that the prevalence of stunting for baby under two years old in Aceh is the highest in Indonesia. This article was based on Foucauldian theory and a qualitative approach, through interviews with 40 families having children under five years old to recall the type of food consumed by all family members for 3 x 24 hours The results show that there is a gap between the practice of fulfilling family food in Aceh and national policies on food and nutrition. The practice of fulfilling family food is focused on carbohydrates and animal protein, while the government promotes the fulfillment of a balanced diet between carbohydrates and proteins (animal and vegetable) with vegetables and fruits. The gap occurs because of differences in the discourses of the power of the body and benefits of food. The community understands that food aims to make the body able to function properly (body productivity discourse). Meanwhile, the government aims for the human body to grow and develop ideally to avoid degenerative diseases (healthy body discourse). Family food fulfillment practices depend on the power of women’s knowledge, especially mothers’ who have the main role in fulfilling family food.